If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 4) + -8 = 20 Reorder the terms: 7(4 + x) + -8 = 20 (4 * 7 + x * 7) + -8 = 20 (28 + 7x) + -8 = 20 Reorder the terms: 28 + -8 + 7x = 20 Combine like terms: 28 + -8 = 20 20 + 7x = 20 Add '-20' to each side of the equation. 20 + -20 + 7x = 20 + -20 Combine like terms: 20 + -20 = 0 0 + 7x = 20 + -20 7x = 20 + -20 Combine like terms: 20 + -20 = 0 7x = 0 Solving 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '7'. x = 0 Simplifying x = 0
| 3.3=m-2.2 | | (3x-3)(x+2)=120 | | (2w+6)w=80 | | 8x=-6x-98 | | 2w+6*w=80 | | x-168-10x=75 | | 3/7=k/42 | | 5x=5x-4 | | 3(a+2)=26-2 | | 3.2=(11-2x)(8.5-2x)x | | -11=1-6b | | 12/m=3/5 | | 2t^2+32t+128= | | 7x-44-2x=61 | | 9z+4-5z=9+3z-9 | | 7x-44-2x=62 | | 3x^2+6x-6=120 | | 7abed-9abed-11abed= | | 3ctgx=1 | | 12=5h-3 | | m+2=0.008 | | -149-5x-11x=43 | | 2tgx=1 | | 2x+14=7x+34 | | -7x-50+4x=16 | | 12+5x(8-4)-2= | | -(3x+3)-3(3y+2)= | | 8(x+2)-(6x-6)=x | | 3-(-4)+5*2=-3 | | 3(y-6)=2(y-1) | | 33-x=17+3x | | X^5=64000000 |